Utilization of Facebook by school children in the apprenticeship seeking process - Sander, Tom; Teh, Phoey Lee *; Sloka, Biruta (Vilnius Gediminas Technical University, 2016)
The search for a practical apprenticeship place can be the first step in the business world for German students. The students have to apply for this placement, as Companies require applicants. Facebook is one of the most often used social networks among the younger generation in Germany, which can provide a direct communication channel between businesses and candidates. The research evaluates the reasons to use Facebook to identify a solid apprenticeship training platform for German students. Research methods applied: scientific publication analysis, survey (by paper-based questionnaire) of German students of the ninth and tenth grade. Analysis of survey data by main indicators of descriptive statistics: arithmetic mean, mode, median, and standard deviations to get an impression of evaluations on analysed aspects by survey respondents. Analysis of variance – ANOVA – is applied to study the difference of the assessments between female and male school children and the differences between the ninth and tenth classes. The existence of correlations between the intensity of use of social network sites (SNS) and the apprenticeship seeking process have been investigated. The results of the research have shown that there are differences in evaluations, on analysed aspects, between female and male school children in the analysed classes on the occasion career entry by the apprenticeship.